Dubai - Barrier, Brooke; Stallings, Doug. (New York : Fodor's Travel Publications, 2009)
A brief travel guide to Dubai in the United Arab Emirates, with maps and information on places to stay, eat, and shop.
Includes index.
Adult
Keywords: Dubai (United Arab Emirates) -- Guidebooks; Dubai (United Arab Emirates) -- Guidebooks